A Robust Graph Theoretic Solution of Routing in Intelligent Networks - Qureshi, M.A. (Hindawi Limited, 2022)
Implementation of robust routing is very critical in network communication. Connecting devices like routers maintain databases for the whole network topology in the routing table. Each router needs to keep these tables updated with the best possible routes so that an efficient communication can always take place in nondelay tolerant intelligent networks that include military and tactical systems, vehicular communication networks, underwater acoustic networks, and intelligent sensor networks. The fast construction of shortest-path tree (SPT) is important to devise an efficient routing in a nondelay tolerant networks. That is why a simple and efficient algorithm is the need of the time. A robust routing solution SPT with OV+E time complexity is proposed to supersede the existing landmark. Â© 2022 Muhammad Aasim Qureshi et al.